Macroeconomics : theory, performance, and policy - Hall, Robert Ernest; Taylor, John B. (New York : Norton & Company, 1986)
MANY EXCITING some say revolutionary--research developments occurred in macroeconomics in the 1970s and 1980s. Their influence is everywhere apparent in the discipline. In this book we have tried to capture the spirit and content of these developments, in a form that is manageable in the intermediate-level college course. Many of the new ideas in macroeconomics draw upon "rational expectations" research. Originally this term referred to a microeconomic model of expectations, much needed for macroeconomic theory, and we use it in this sense. As such, its influence permeates the book. Each of the chapters on consumption, investment, foreign trade, and money has the theory of rational expectations intrinsic to its discussion. So do the chapters on the new classical theories, forward-looking price setting, and policy rules.
The macroeconomy -- Measuring economic performance : output and income -- Monitoring the economy : inflation and employment -- Aggregate demand -- Aggregate supply and price adjustment -- Macroeconomic policy : a first look -- Consumption demand and investment demand -- Foreign trade and the exchange rate -- The government's influence on aggregate demand -- The monetary system -- Aggregate supply and economic growth -- New classical theory -- The theory of wage and price rigidities -- Aggregate dynamics and price adjustment -- Designing and maintaining a good macro policy -- Macroeconomic policy in the world economy.
Includes index.
Keywords: MACROECONOMICS